Production of Monoclonal Antibodies. (16th February 2018) - Yokoyama, Wayne M.; Christensen, Michelle; Santos, Gary Dos; Miller, Diane; Ho, Jason; Wu, Tao; Dziegelewski, Michael; Neethling, Francisca A.
Abstract: This unit describes the production of monoclonal antibodies beginning with immunization, cell fusion, and selection. Support protocols are provided for screening primary hybridoma supernatants for antibodies of desired specificity, establishment of stable hybridoma lines, cloning of these B cell lines by limiting dilution to obtain monoclonal lines, and preparation of cloning/expansion medium. An alternate protocol describes cell fusion and one‐step selection and cloning of hybridomas utilizing a semi‐solid methylcellulose‐based medium (ClonaCell‐HY from StemCell Technologies). Curr. Protoc. Immunol . 102:2.5.1‐2.5.29. © 2013 by John Wiley & Sons, Inc.